Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.2174/187152709789541998
|View full text |Cite
|
Sign up to set email alerts
|

Cross Currents in Protein Misfolding Disorders: Interactions and Therapy

Abstract: Protein Misfolding Disorders (PMDs) are a group of diseases characterized by the accumulation of abnormally folded proteins. Despite the wide range of proteins and tissues involved, PMDs share similar molecular and pathogenic mechanisms. Several epidemiological, clinical and experimental reports have described the co-existence of PMDs, suggesting a possible cross-talk between them. A better knowledge of the molecular basis of PMDs could have important implications for understanding the mechanism by which the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 94 publications
2
45
0
Order By: Relevance
“…After acute traumatic injury in animal models, TDP-43 expression is upregulated and TDP-43 relocates from the neuronal nucleus to accumulate in the neuronal cytoplasm [134, 135] TDP-43 binds to many cellular transcripts including tau and alpha synuclein, and its dysregulation may underlie some of the pathologies seen with these proteins [162]. In particular, TDP-43 may influence tau iso-form expression [136]. There is also evidence that alteration in tau protein metabolism including hyperphosphorylation, tau phosphatase resistance, and deposition of PHF-tau intracellular aggregates may be found in diseases characterized by abnormal TDP-43 metabolism, such as ALS [177].…”
Section: Adverse Neuropathological Outcomes Associated With Sports Pamentioning
confidence: 99%
“…After acute traumatic injury in animal models, TDP-43 expression is upregulated and TDP-43 relocates from the neuronal nucleus to accumulate in the neuronal cytoplasm [134, 135] TDP-43 binds to many cellular transcripts including tau and alpha synuclein, and its dysregulation may underlie some of the pathologies seen with these proteins [162]. In particular, TDP-43 may influence tau iso-form expression [136]. There is also evidence that alteration in tau protein metabolism including hyperphosphorylation, tau phosphatase resistance, and deposition of PHF-tau intracellular aggregates may be found in diseases characterized by abnormal TDP-43 metabolism, such as ALS [177].…”
Section: Adverse Neuropathological Outcomes Associated With Sports Pamentioning
confidence: 99%
“…In addition to the progressive death of neurons, neurodegenerative diseases cause accumulation of aberrantly-folded “key” disease proteins (Morales and Green, 2009; Aguzzi and O'Connor, 2010; Perry et al, 2012), which individually characterize each of these conditions, including amyloid β in Alzheimer's disease (AD), α synuclein in Parkinson's disease (PD) and prion protein (PrP Sc ) in prion diseases such as Creutzfeldt-Jakob disease (CJD) (Prusiner, 1982; Olanow and Prusiner, 2009). These aggregates are considered hallmarks of neurodegenerative diseases (Ashe and Aguzzi, 2013; Prusiner, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This study has demonstrated that the seeding potency of homologous AA fibrils is higher than that of heterologous fibrils. Homologous seeding has been documented for most proteins implicated in misfolding diseases [16,17]. In this study, peak AA deposition was observed 20 days after AA fibril administration.…”
Section: Discussionmentioning
confidence: 56%